Positive electrode for power storage device, method for producing positive electrode for power storage device, and power storage device
By applying a polyether copolymer solution to the positive electrode active material layer and impregnating it within the electrode, the issues of gas generation and resistance increase in power storage devices are mitigated, leading to improved battery life and cycle characteristics.
Patent Information
- Application Number
- JP2020171258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-10-09
AI Technical Summary
In power storage devices, gas generation and resistance increase significantly impact battery life, necessitating strict control over water contamination, electrolyte voltage resistance, and initial aging.
A positive electrode is developed by applying a solution of a specific polyether copolymer onto the positive electrode active material layer and impregnating it inside the electrode, which reduces gas generation and resistance increases during charging and discharging.
The approach effectively reduces decomposition gas on the positive electrode surface, lowers resistance rise, and improves charge/discharge cycle characteristics, resulting in enhanced battery life.
Smart Images

Figure 0007658074000001 
Figure 0007658074000002 
Figure 0007658074000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode for an electricity storage device, a method for manufacturing a positive electrode for an electricity storage device, and an electricity storage device, and more particularly to a positive electrode for a lithium ion secondary battery, a method for manufacturing a positive electrode, and a lithium ion secondary battery. [Background technology]
[0002] Recent microelectronics has become prominent, as typified by power sources for memory backup in various electronic devices. That is, as batteries are housed in electronic devices and integrated with electronic elements, there is a demand for smaller, lighter batteries and power storage devices with higher energy density. Furthermore, as various small electronic devices such as camcorders, portable communication devices, and laptop computers have become smaller and lighter in recent years, there is an increasing demand for high-energy density power storage devices as power sources for driving these devices, and research and development into these devices is being actively conducted.
[0003] High-energy density electricity storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, and electric double-layer capacitors comprise a pair of electrodes and a separator impregnated with an electrolyte solution, and are used in a variety of industrial and consumer electric and electronic devices.
[0004] Conventionally, for power storage devices utilizing electrochemical reactions, such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors, it is essential to further increase the capacity and improve safety as well as to extend the life of the devices. To achieve this, improvements in the positive electrode are required.
[0005] In recent years, attempts have been made to improve the binder. It has been proposed to improve the adhesiveness between active materials, between the active material and the conductive assistant, and between the active material and the current collector, thereby extending the life of the battery (see Patent Document 1).
[0006] A secondary battery with excellent high-capacity cycle charge / discharge characteristics has been disclosed, in which the surface of a positive electrode material is covered with a polymer solid electrolyte composition using an electrolyte salt compound that is a combination of a polyether copolymer and lithium bis(oxalato)borate with another lithium salt compound, and one or both of the polymer solid electrolyte and the positive electrode material contain a compound having a phenol structure in which both ortho positions are substituted with tert-butyl groups (see Patent Document 2).
[0007] Furthermore, in order to reduce size and increase capacity, the expansion of the electrode due to gas generation caused by contact between the electrolyte and the active material has become a problem, and this problem is particularly prominent when a Ni-based positive electrode active material is used. Therefore, a technology has been disclosed in which carboxymethylcellulose is used as a polymer to coat the Ni-based positive electrode active material, but carboxymethylcellulose has low ionic conductivity, and increasing the coating thickness inhibits the movement of lithium ions at the interface with the positive electrode active material, which may reduce battery performance. In addition, there is a problem that reducing the amount of coating reduces the effect of suppressing gas generation. (See Patent Document 3) [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2013 / 180103 [Patent Document 2] Patent No. 6246019 [Patent Document 3] Patent No. 5079025 Summary of the Invention [Problem to be solved by the invention]
[0009] In electricity storage devices, particularly in electricity storage devices using non-aqueous electrolytes, gas generation and resistance increase have a significant effect on deterioration of life, so that moisture contamination, voltage resistance of the electrolyte, and initial aging must be strictly controlled. The present invention aims to provide a positive electrode that can improve battery life by reducing gas generation and resistance increase when used in an electrode of an electricity storage device. [Means for solving the problem]
[0010] As a result of extensive investigations to achieve the above-mentioned object, the inventors discovered that a positive electrode in which a solution of a specific polyether copolymer is applied onto a positive electrode active material layer and the polyether copolymer is impregnated and supported inside the electrode has the effect of reducing gas generation that occurs during charging and discharging of an electricity storage device and reducing resistance increases, and thus completed the present invention.
[0011] That is, the present invention relates to the following.
[0012] Item 1 Formula (1): [ka] [In the formula, R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ) R 1 , R 2 , R 3 is a hydrogen atom or -CH2O(CH2CH2O)nR 4 where n and R 4 is R 1 , R 2 , R 3 may differ between R 4 is an alkyl group having 1 to 12 carbon atoms or an aryl group, and n is an integer of 0 to 12. 0 to 95 mol % of a repeating unit derived from a monomer represented by the formula: Formula (2): [ka] 95 to 5 mol % of repeating units derived from a monomer represented by the formula: Formula (3) [ka] [In the formula, R 5 is a group having an ethylenically unsaturated group. a positive electrode for an electricity storage device, comprising at least a polyether copolymer having 0 to 20 mol % of a repeating unit derived from a monomer represented by the following formula: Item 2. The positive electrode for an electricity storage device according to item 1, wherein the positive electrode active material layer contains a conductive assistant and a binder. Item 3. A method for producing a positive electrode for an electricity storage device according to item 1 or 2, comprising the step of applying the polyether copolymer in a solution state dissolved in a solvent to a positive electrode active material layer to impregnate and support the polyether copolymer in the positive electrode active material layer. Item 4. The method for producing a positive electrode for an electricity storage device according to item 3, wherein the solvent is at least one selected from the group consisting of water, alcohol, acetone, acetonitrile, methyl ethyl ketone, toluene, and N-methyl-2-pyrrolidone. Item 5. An electricity storage device comprising the positive electrode according to item 1 or 2. Effect of the Invention
[0013] According to the present invention, the amount of decomposition gas of the electrolyte solution generated on the surface of the positive electrode during charge-discharge cycles or when left in a fully charged state is reduced, and an increase in resistance is also reduced, thereby improving the charge-discharge cycle characteristics and providing a positive electrode with excellent life characteristics.
[0014] The configuration of the present invention will be described in detail below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, the electricity storage device includes secondary batteries (lithium ion secondary batteries, nickel-hydrogen secondary batteries, etc.) and electrochemical capacitors.
[0016] The electricity storage device according to the present invention is characterized in that at least the positive electrode carries the polyether copolymer described below, and is laminated with a negative electrode serving as a counter electrode via a separator.
[0017] <Polyether copolymer> The compound of formula (1) can be obtained from a commercial product or can be easily synthesized by a general ether synthesis method from epihalohydrin and alcohol. Examples of the commercially available compounds include propylene oxide, butylene oxide, methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, tertiary butyl glycidyl ether, benzyl glycidyl ether, 1,2-epoxydodecane, 1,2-epoxyoctane, 1,2-epoxyheptane, 2-ethylhexyl glycidyl ether, 1,2-epoxydecane, 1,2-epoxyhexane, glycidyl phenyl ether, 1,2-epoxypentane, and glycidyl isopropyl ether. Among these commercial products, propylene oxide, butylene oxide, methyl glycidyl ether, ethyl glycidyl ether, butyl glycidyl ether, and glycidyl isopropyl ether are preferred, and propylene oxide, butylene oxide, methyl glycidyl ether, and ethyl glycidyl ether are particularly preferred. In the monomer represented by formula (1) obtained by synthesis, R is -CH2O(CR 1 R 2 R 3 ) is preferred, R 1 , R 2 , R 3 At least one of the following is -CH2O(CH2CH2O)nR 4 It is preferable that R 4 is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably 1 to 4 carbon atoms. n is preferably an integer of 0 to 6, and more preferably 0 to 4.
[0018] The compound of formula (2) is ethylene oxide. The compound of formula (2) is a basic chemical and is readily available commercially.
[0019] In the compound of formula (3), R 5 Examples of the alkyl group may be a hydrocarbon group having a double bond, in particular a cyclic hydrocarbon group having a double bond, or CH2=CH-A 1 -(A 1 may be a direct bond or a hydrocarbon group having 1 to 30 carbon atoms, such as an alkylene group). The compound of formula (3) is commercially available or can be easily synthesized by a general ether synthesis method from epihalohydrin and alcohol. Examples of the glycidyl ether include allyl glycidyl ether, 4-vinylcyclohexyl glycidyl ether, α-terpinyl glycidyl ether, cyclohexenyl methyl glycidyl ether, p-vinylbenzyl glycidyl ether, allyl phenyl glycidyl ether, vinyl glycidyl ether, 3,4-epoxy-1-butene, 3,4-epoxy-1-pentene, 4,5-epoxy-2-pentene, 1,2-epoxy-5,9-cyclododecadiene, 3,4-epoxy-1-vinylcyclohexene, 1,2-epoxy-5-cyclooctene, glycidyl acrylate, glycidyl methacrylate, glycidyl sorbate, glycidyl cinnamate, glycidyl crotonate, and glycidyl-4-hexenoate. Of these, allyl glycidyl ether, vinyl glycidyl ether, glycidyl acrylate, and glycidyl methacrylate are preferred.
[0020] The polyether copolymer used in the positive electrode of the present invention is (A): A repeating unit derived from a monomer of formula (1) [ka] [In the formula, R is an alkyl group having 1 to 12 carbon atoms, or -CH2O(CR 1 R 2 R 3 ) R 1 , R 2 , R 3is a hydrogen atom or -CH2O(CH2CH2O)nR 4 where n and R 4 is R 1 , R 2 , R 3 may differ between R 4 represents an alkyl group having 1 to 12 carbon atoms or an aryl group which may have a substituent, and n represents an integer of 0 to 12. (B): a repeating unit derived from a monomer of formula (2), and [ka] and (C): a repeating unit derived from a monomer of formula (3), [ka] [In the formula, R 5 is a substituent containing a group having an ethylenically unsaturated group. It consists of:
[0021] Here, each of the repeating units (A) and (C) may be derived from two or more kinds of monomers.
[0022] The synthesis of the polyether copolymer of the present invention can be carried out as follows. A polyether copolymer can be obtained by reacting each monomer with stirring at a reaction temperature of 10 to 120°C in the presence or absence of a solvent using a coordinated anion initiator such as an organoaluminum-based catalyst system, an organozinc-based catalyst system, or an organotin-phosphate ester condensate catalyst system as a ring-opening polymerization catalyst, or an anion initiator such as potassium alkoxide, diphenylmethyl potassium, or potassium hydroxide containing K+ as a counter ion. From the viewpoint of the degree of polymerization or the properties of the resulting copolymer, a coordinated anion initiator is preferred, and among them, an organotin-phosphate ester condensate catalyst system is particularly preferred because it is easy to handle.
[0023] In the polyether copolymer of the present invention, the molar ratios of the repeating units (1), (2), and (3) are suitably (1) 5-95 mol%, (2) 95-5 mol%, and (3) 0-20 mol%, preferably (1) 7-90 mol%, (2) 92-10 mol%, and (3) 0-17 mol%, more preferably (1) 10-80 mol%, (2) 90-20 mol%, and (3) 0-15 mol%. If the repeating unit (2) exceeds 95 mol%, the glass transition temperature increases and the oxyethylene chain crystallizes, resulting in a significant deterioration in the ionic conductivity of the solid electrolyte. It is generally known that ionic conductivity is improved by reducing the crystallinity of polyethylene oxide, but the polyether copolymer of the present invention is far superior in this respect.
[0024] The molecular weight of the polyether copolymer of the present invention is not particularly limited, but the weight average molecular weight is preferably 100,000 to 2,500,000. By setting the weight average molecular weight within this range, the viscosity of the polymer solution in which the polyether copolymer is dissolved becomes appropriate, and better charge / discharge characteristics can be obtained as an electricity storage device.
[0025] The polyether copolymer of the present invention may be either a block copolymer or a random copolymer, with the random copolymer being preferred since it has a greater effect of reducing the crystallinity of polyethylene oxide.
[0026] In the positive electrode of the present invention, the polyether copolymer supported thereon may be a crosslinked product of the above-mentioned polyether copolymer.
[0027] The crosslinked product of the polyether copolymer is a crosslinked product obtained by applying heat or irradiating with active energy rays such as ultraviolet rays.
[0028] In the present invention, a solution obtained by dissolving a polyether copolymer and, if necessary, a photoreaction initiator and a thermal polymerization initiator is used, and then the solution is applied to a positive electrode active material layer, and then the solution is irradiated with active energy rays such as ultraviolet rays or is heated, so that the crosslinked product of the polyether copolymer can be supported on the positive electrode active material layer. A crosslinking assistant can also be added to the solution obtained by dissolving the polyether copolymer, if necessary.
[0029] Examples of photoinitiators that can be used in the present invention include alkylphenones, benzophenones, acylphosphine oxides, titanocenes, triazines, bisimidazoles, and oxime esters. Preferably, alkylphenones, benzophenones, and acylphosphine oxides are used. Two or more of the above-mentioned compounds can be used in combination as the photoinitiator.
[0030] Examples of the thermal polymerization initiator that can be used in the present invention include radical initiators selected from organic peroxides and azo compounds. Preferably, the organic peroxides include thermal polymerization initiators such as ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, and peroxyesters, and the azo compounds include thermal polymerization initiators such as azonitrile compounds, azoamide compounds, and azoamidine compounds. More preferably, organic peroxide initiators are used, and two or more of these compounds can be used in combination.
[0031] The amount of the photoreaction initiator or thermal polymerization initiator used in the present invention is preferably within a range of 0.1 to 10 parts by mass, and more preferably 0.1 to 4.0 parts by mass, based on 100 parts by mass of the polyether copolymer.
[0032] In the present invention, a crosslinking coagent may be used in combination with the photoreaction initiator. The crosslinking coagent is usually a polyfunctional compound (for example, a compound containing at least two CH2=CH-, CH2=CH-CH2-, or CF2=CF-).
[0033] The amount of the crosslinking aid used in the present invention is preferably within a range of 0.1 to 30 parts by mass, and more preferably 0.5 to 20 parts by mass, based on 100 parts by mass of the polyether copolymer.
[0034] The active energy rays used for crosslinking the polyether copolymer used in the present invention may be ultraviolet light, visible light, electron beams, etc. Among these, ultraviolet light is particularly preferred in view of the cost of the equipment and ease of control.
[0035] <Positive electrode> The positive electrode used in the present invention is formed from a positive electrode current collector, a positive electrode active material layer containing at least a positive electrode active material, and a polyether copolymer.
[0036] The material of the current collector used in the electrode for the power storage device of the present invention can be, for example, metal, carbon, conductive polymer, etc., and metal is preferably used. As the metal for the current collector, aluminum, platinum, nickel, tantalum, titanium, stainless steel, copper, other alloys, etc. are usually used. Among these, it is preferable to use copper, aluminum, or an aluminum alloy in terms of conductivity and voltage resistance, and as the current collector used for the positive electrode, a metal foil such as aluminum foil is preferably used.
[0037] As the positive electrode active material, metal oxides, metal sulfides, or specific polymers can be used depending on the type of battery desired.
[0038] For example, in the case of a lithium battery utilizing the dissolution and precipitation of lithium, metal sulfides or oxides not containing lithium, such as TiS2, MoS2, NbS2, and V2O5, as well as polymers such as polyacetylene and polypyrrole, can be used.
[0039] In the case of a lithium-ion battery using doping and undoping of lithium ions, a lithium composite oxide represented by LixMO2 (where M represents one or more transition metals, x varies depending on the charge and discharge state of the battery, and is usually 0.05 or more and 1.10 or less), or a lithium composite phosphate represented by LixMPO4 (where M represents one or more transition metals, x varies depending on the charge and discharge state of the battery, and is usually 0.05 or more and 1.10 or less), etc. can be used. As the transition metal M constituting this lithium composite oxide or lithium phosphate, Co, Ni, Mn, Al, Fe, etc. are preferable. Specific examples of such lithium composite oxides include LiCoO2, LiNiO2, LiNi y Co z Mn 1-y-z O2 (where 0 < y, z < 1), LiNi y Co z Al 1-y-z O2 (where 0 < y, z < 1), LiMn2O4, LiFePO4, etc. can be mentioned.
[0040] The lithium composite oxide can generate a high voltage and becomes a cathode active material excellent in energy density. A plurality of these cathode active materials may be used in combination as the cathode active material. Further, when forming the cathode active material using the above cathode active material, known binders, etc. can be added as long as the effects of the present invention are not inhibited.
[0041] As the binder that can be used for the cathode active material layer, for example, one or more compounds selected from fluorine-based binders, acrylic rubbers, modified acrylic rubbers, styrene-butadiene rubbers, acrylic polymers, and vinyl polymers can be used. Further, since an acrylic polymer has oxidation resistance, sufficient adhesiveness in a small amount, and flexibility can be obtained for the electrode plate, it is preferable to use an acrylic polymer. In particular, an aqueous binder that dissolves in water is preferable because it does not dissolve organic active materials. These binders are preferably added to the cathode active material in an amount of 0.1 to 10% by mass, more preferably 0.5 to 5% by mass.
[0042] The positive electrode active material layer may contain, in addition to the above, a conductive assistant, a solvent, and a thickener. Examples of the conductive assistant include carbon compounds such as conductive carbon such as acetylene black, ketjen black, carbon fiber, and graphite, conductive polymers, and metal powders, and conductive carbon is particularly preferred. As the solvent, any solvent can be used as long as it can dissolve the positive electrode active material and the binder, and preferably water, N-methyl-2-pyrrolidone, and the like are used. Examples of the thickener include carboxymethylcellulose, methylcellulose, hydroxyethylcellulose, and the like, or alkali metal salts thereof, and polyethylene oxide. Examples of the thickener include carboxymethylcellulose, methylcellulose, hydroxyethylcellulose, and the like, or alkali metal salts thereof, and polyethylene oxide.
[0043] In the positive electrode of the present invention, the method of forming the positive electrode active material layer on the current collector is not particularly limited, but includes a method of laminating a sheet-shaped positive electrode active material layer on the current collector (kneading sheet molding method); a method of applying a paste-like positive electrode active material powder or the like on the current collector by a doctor blade method or a silk screen method, etc., and drying it (wet molding method); a method of preparing a positive electrode active material powder or the like, and forming a sheet on the current collector and rolling it (dry molding method), etc. Among them, the wet molding method and the dry molding method are preferred, and the wet molding method is more preferred.
[0044] <Method of supporting polyether copolymer on positive electrode active material layer> In the positive electrode of the present invention, the method of supporting the polyether copolymer on the positive electrode active material layer is not particularly limited, but examples thereof include a method of dissolving the polyether copolymer in water or an organic solvent, applying a solution obtained by dissolving the polyether copolymer in water or an organic solvent onto the positive electrode active material layer, and then drying the solution, and a method of spraying a solution obtained by dissolving the polyether copolymer in water or an organic solvent onto the positive electrode active material layer, and then drying the solution, etc. The positive electrode is press-molded before and after supporting the polyether copolymer.
[0045] The method of applying the polyether copolymer used in the present invention to the positive electrode active material layer is not particularly limited, but the solution obtained by dissolving the polyether copolymer in a solvent can be applied to the porous film by a suitable method from microgravure, slot die, silk screen, knife coating, etc. depending on the solution viscosity and the target coating film thickness, and can also be applied by spray coating using a sprayer. As a drying method, drying equipment such as a heater type, hot air drying type, infrared irradiation type, and vacuum type can be used. To remove excess solvent, for example, drying is performed at 50 to 150 ° C (especially at 80 ° C) under normal pressure or in a vacuum state.
[0046] The solvent used in the present invention when applying the polyether copolymer to the positive electrode active material layer is one capable of dissolving the polyether copolymer and can be selected from water, alcohol, acetone, acetonitrile, methyl ethyl ketone, toluene and N-methyl-2-pyrrolidone. These solvents may be used alone or in combination of two or more.
[0047] The concentration of the polyether copolymer in the solution is not particularly limited, but is preferably 0.05 to 30% by mass, and more preferably 0.1 to 20% by mass.
[0048] In the present invention, the amount of the polyether copolymer applied to the positive electrode active material layer is preferably 0.01 to 5 parts by mass, more preferably 0.01 to 4 parts by mass, and even more preferably 0.01 to 3 parts by mass per 100 parts by mass of the positive electrode active material. If the amount is less than this range, the effects of reducing gas generation and resistance increase cannot be obtained, and if the amount is more than this range, the charge / discharge capacity and charge / discharge cycle characteristics will decrease.
[0049] If necessary, the crosslinking reaction of the polyether copolymer can be carried out by heating for about 10 minutes to 24 hours at a temperature setting of room temperature to about 200° C. If ultraviolet light is used, a xenon lamp, a mercury lamp, a high-pressure mercury lamp, or a metal halide lamp can be used, and the crosslinking reaction can be carried out by irradiating the electrolyte with ultraviolet light having a wavelength of 365 nm and a light intensity of 1 to 50 mW / cm2 for 0.1 to 30 minutes.
[0050] If necessary, the crosslinking reaction of the polyether copolymer may be carried out before, during, or after drying of the positive electrode active material layer after applying a solution obtained by dissolving a polyether copolymer containing a photoreaction initiator and a thermal polymerization initiator to the positive electrode active material layer.
[0051] <Negative electrode> The negative electrode used in the present invention is formed from a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material and a binder.
[0052] The material of the current collector used in the negative electrode of the present invention may be, for example, a metal, carbon, a conductive polymer, etc., and is preferably a metal. As the metal for the current collector, aluminum, platinum, nickel, tantalum, titanium, stainless steel, copper, other alloys, etc. are usually used. Among these, a metal foil such as a copper foil is preferably used in terms of electrical conductivity and voltage resistance.
[0053] As the negative electrode active material, for example, in the case of a lithium battery utilizing dissolution and precipitation of lithium, metallic lithium, a lithium alloy capable of absorbing and releasing lithium, or the like can be used.
[0054] In the case of a lithium ion battery utilizing doping and dedoping of lithium ions, carbon materials based on non-graphitizable carbon or graphite can be used. More specifically, carbon materials such as graphite, mesocarbon microbeads, carbon fibers such as mesophase carbon fiber, pyrolytic carbon, cokes (pitch coke, needle coke, petroleum coke), glassy carbon, organic polymer compound sintered bodies (phenolic resin, furan resin, etc., sintered at an appropriate temperature and carbonized), and activated carbon can be used. When forming a negative electrode from such materials, known binders can be added.
[0055] The binder used in the negative electrode active material layer may be, for example, one or more compounds selected from fluorine-based binders, acrylic rubber, modified acrylic rubber, styrene-butadiene rubber, acrylic polymers, and vinyl polymers. In addition, it is preferable to use acrylic polymers because they have oxidation resistance, sufficient adhesion with a small amount, and flexibility in the electrode plate. In particular, water-based binders that dissolve in water are preferable because they do not dissolve organic active materials. These binders are added preferably in an amount of 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, relative to the negative electrode active material.
[0056] The negative electrode active material layer may contain, in addition to the above, a conductive assistant, a solvent, a thickener, etc. Examples of the conductive assistant include carbon compounds such as conductive carbons such as acetylene black, ketjen black, carbon fiber, graphite, etc., conductive polymers, metal powders, etc., and conductive carbon is particularly preferred. As the solvent, any solvent can be used as long as it can dissolve the negative electrode active material and the binder, and water, N-methyl-2-pyrrolidone, etc. are preferably used. In addition, as the thickener, carboxymethylcellulose, methylcellulose, hydroxyethylcellulose, etc., or alkali metal salts thereof, etc. are used.
[0057] The negative electrode of the present invention is obtained by forming a negative electrode active material layer on a current collector. Specifically, there are a method of laminating a negative electrode active material layer formed into a sheet shape on a current collector (kneading sheet forming method); a method of applying a paste-like negative electrode active material powder or the like on a current collector by a doctor blade method or a silk screen method, and drying it (wet forming method); a method of preparing a negative electrode active material powder or the like, forming a sheet on a current collector, and roll pressing it (dry forming method), and the like. Among them, the wet forming method and the dry forming method are preferred, and the wet forming method is more preferred.
[0058] <Electrolyte> The electrolyte solution is one in which an electrolyte salt is dissolved in an aprotic organic solvent, and a room temperature molten salt (ionic liquid) can also be used.
[0059] The electrolyte salt compound used in the electrolyte solution usable in the present invention is preferably compatible with the mixture of the crosslinked polyether copolymer and the aprotic organic solvent, where "compatible" means a state in which the electrolyte salt does not crystallize or precipitate.
[0060] In the present invention, the following electrolyte salt compounds are preferably used: a cation selected from a metal cation, an ammonium ion, an amidinium ion, and a guanidinium ion, and a chloride ion, a bromide ion, an iodide ion, a perchlorate ion, a thiocyanate ion, a tetrafluoroborate ion, a nitrate ion, an AsF6 - , PF6 - , stearylsulfonate ion, octyl sulfonate ion, dodecylbenzenesulfonate ion, naphthalenesulfonate ion, dodecylnaphthalenesulfonate ion, 7,7,8,8-tetracyano-p-quinodimethane ion, X1SO3 - , [(X1SO2)(X2SO2)N] - , [(X1SO2)(X2SO2)(X3SO2)C] - , and [(X1SO2)(X2SO2)YC] -and an anion selected from the group consisting of: wherein X1, X2, X3, and Y are electron-withdrawing groups. Preferably, X1, X2, and X3 are each independently a perfluoroalkyl group having 1 to 6 carbon atoms or a perfluoroaryl group having 6 to 18 carbon atoms, and Y is a nitro group, a nitroso group, a carbonyl group, a carboxyl group, or a cyano group. X1, X2, and X3 may be the same or different.
[0061] The metal cation may be a transition metal cation. Preferably, a metal cation selected from Mn, Fe, Co, Ni, Cu, Zn, and Ag metals is used. Also, a metal cation selected from Li, Na, K, Rb, Cs, Mg, Ca, and Ba metals may be used to obtain favorable results. Two or more of the above-mentioned compounds may be used in combination as the electrolyte salt compound. In particular, in lithium ion secondary batteries, a Li salt compound is preferably used as the electrolyte salt compound.
[0062] The Li salt compound is a Li salt compound having a wide potential window, such as those generally used in lithium ion secondary batteries. Examples include, but are not limited to, LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, and LiN[CF3SC(C2F5SO2)3]2. These may be used alone or in combination of two or more.
[0063] Furthermore, as the electrolyte salt or the electrolyte solution, a room temperature molten salt can be used.
[0064] Room temperature molten salt refers to salt that is at least partially liquid at room temperature, and room temperature refers to the temperature range in which a power supply is expected to operate normally. The temperature range in which a power supply is expected to operate normally has an upper limit of about 120°C, or in some cases about 60°C, and a lower limit of about -40°C, or in some cases about -20°C.
[0065] Room temperature molten salts are also called ionic liquids, and pyridine-based, aliphatic amine-based, and alicyclic amine-based quaternary ammonium organic cations are known. Examples of quaternary ammonium organic cations include imidazolium ions such as dialkylimidazolium and trialkylimidazolium, tetraalkylammonium ions, alkylpyridinium ions, pyrazolium ions, pyrrolidinium ions, and piperidinium ions. In particular, imidazolium cations are preferred.
[0066] Examples of imidazolium cations include, but are not limited to, a 1,3-dimethylimidazolium ion, a 1-ethyl-3-methylimidazolium ion, a 1-methyl-3-ethylimidazolium ion, a 1-methyl-3-butylimidazolium ion, a 1-butyl-3-methylimidazolium ion, a 1,2,3-trimethylimidazolium ion, a 1,2-dimethyl-3-ethylimidazolium ion, a 1,2-dimethyl-3-propylimidazolium ion, and a 1-butyl-2,3-dimethylimidazolium ion.
[0067] These room-temperature molten salts having cations may be used alone or in combination of two or more.
[0068] In the present invention, the content of the electrolyte salt is preferably 0.1 to 3.0 mol / L, and particularly preferably 1.0 to 2.0 mol / L. If the content of the electrolyte salt is less than 0.1 mol / L, the resistance of the electrolyte solution is high and the large current / low temperature discharge characteristics are deteriorated, whereas if the content exceeds 3.0 mol / L, the solubility is poor and crystals are precipitated.
[0069] The electrolyte solution used in the power storage device of the present invention is not particularly limited. In general, an electrolyte salt dissolved in an aprotic organic solvent is used. Specifically, such an aprotic organic solvent may be propylene carbonate, ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, γ-butyrolactone, tetrahydrofuran, 1,3-dioxolane, dipropyl carbonate, diethyl ether, sulfolane, methyl sulfolane, acetonitrile, propyl nitrile, anisole, acetate, propionate, or the like, and may be used alone or in combination of two or more.
[0070] <Method of manufacturing electricity storage device> The electricity storage device of the present invention can be produced by stacking a positive electrode and a negative electrode, which are electrodes formed by forming the electrode composition on a current collector, with the above-mentioned separator interposed between them, and injecting an electrolyte solution. EXAMPLES
[0071] Specific embodiments for carrying out the present invention will be described below with reference to examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0072] [Synthesis Example (Production of Polyether Copolymerization Catalyst)] 10 g of tributyltin chloride and 35 g of tributylphosphate were placed in a three-neck flask equipped with a stirrer, a thermometer, and a distillation apparatus, and heated at 250°C for 20 minutes while stirring under a nitrogen stream to remove the distillate and obtain a solid condensation product as a residue. This was used as a polymerization catalyst in the following polymerization examples.
[0073] The monomer equivalent composition of polyether copolymer is 1 It was determined by H NMR spectroscopy. The molecular weight of the polyether copolymer was measured by gel permeation chromatography (GPC), and the weight average molecular weight was calculated based on standard polystyrene. The GPC measurement was performed at 60°C using Shimadzu RID-6A, Showa Denko Showdex KD-807, KD-806, KD-806M, and KD-803 columns, and DMF as a solvent.
[0074] [Polymerization Example 1] The inside of a 3 L glass four-neck flask was replaced with nitrogen, and 1 g of the condensation product shown in the catalyst synthesis example was added as a polymerization catalyst and a glycidyl ether compound (a) adjusted to a water content of 10 ppm or less: [ka] 160g of ethylene oxide, 15g of allyl glycidyl ether, and 1000g of n-hexane as a solvent were charged, and 125g of ethylene oxide was added successively while monitoring the polymerization rate of compound (a) by gas chromatography. The polymerization temperature was set to 20°C, and the reaction was carried out for 10 hours. The polymerization reaction was stopped by adding 1mL of methanol. After removing the polymer by decantation, it was dried at 40°C under normal pressure for 24 hours and then at 45°C under reduced pressure for 10 hours to obtain 280g of polymer. The weight average molecular weight and monomer-equivalent composition analysis results of the obtained polyether copolymer are shown in Table 1.
[0075] [Polymerization Example 2] The same procedure was carried out as in Polymerization Example 1, except that glycidyl ether compound (a) and allyl glycidyl ether were not added, but 130 g of propylene oxide and 0.1 g of n-butanol were added, and 170 g of ethylene oxide was successively added to polymerize the mixture, to obtain 285 g of polymer. The weight average molecular weight and monomer-equivalent composition analysis results of the obtained polyether copolymer are shown in Table 1.
[0076] [Polymerization Example 3] The same procedure was carried out as in Polymerization Example 1, except that glycidyl ether compound (a) and allyl glycidyl ether were not added, and 300 g of ethylene oxide and 0.5 g of n-butanol were charged and polymerized to obtain 280 g of polymer. The weight average molecular weight and monomer-equivalent composition analysis results of the obtained polyether copolymer are shown in Table 1.
[0077] [Table 1]
[0078] [Example 1] Preparation of lithium ion secondary battery 1 <Positive electrode 1> The positive electrode active material is LiNi with an average particle size of 10 μm. 0.5 Co 0.2 Mn 0.3 O2 was used. 90 parts by mass of this positive electrode active material was mixed with 3 parts by mass of spherical carbon particles produced by pyrolysis of acetylene as a conductive assistant, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent, and the mixture was stirred for 1 hour using a stainless steel ball mill, and then coated on an aluminum current collector using a bar coater with a gap of 100 μm, dried at 80° C. in a vacuum for 12 hours or more, and then roll-pressed to form a positive electrode sheet. Further, on this sheet, a solution in which 1 part by mass of the polyether copolymer obtained in Polymerization Example 1, 0.02 parts by mass of benzophenone as a photoreaction initiator, and 0.1 parts by mass of N,N'-m-phenylene bismaleimide as a crosslinking aid were dissolved in 99 parts by mass of acetonitrile was spray-coated on the positive electrode active material layer, and the sheet was left to dry at 25°C for 5 hours, and then dried at 60°C for 10 hours in a normal pressure dryer. Next, with the surface covered with a laminate film, the sheet was exposed to a high-pressure mercury lamp (30 mW / cm) manufactured by GS Yuasa Corporation. 2 ) for 30 seconds to cause crosslinking, thereby producing a positive electrode 1 carrying 0.01 part by mass of a crosslinked product of the polyether copolymer per 100 parts by mass of the positive electrode active material.
[0079] <Negative electrode> 90 parts by weight of graphite powder (porous structure material), 10 parts by weight of polyvinylidene fluoride, and 100 parts by weight of N-methyl-2-pyrrolidone were used as a solvent and stirred for 1 hour using a stainless steel ball mill. The mixture was then applied to a copper current collector using a bar coater with a 50 μm gap, dried at 80°C in a vacuum for 12 hours or more, and then roll-pressed to form a negative electrode.
[0080] <separator> A porous polyethylene membrane with a thickness of 15 μm was used.
[0081] <Electrolyte solution> A non-aqueous electrolyte solution was prepared by mixing 15 parts by mass of ethylene carbonate (EC), 15 parts by mass of propylene carbonate (PC), 50 parts by mass of diethyl carbonate, and 20 parts by mass of LiBF4 as an electrolyte salt.
[0082] Finally, the positive electrode 1 and the negative electrode were pressure-bonded via a separator to form a laminate, which was then housed in an aluminum laminate and a non-aqueous electrolyte solution was injected to produce a lithium ion secondary battery 1.
[0083] [Example 2] Preparation of lithium ion secondary battery 2 <Positive electrode 2> The positive electrode active material is LiNi with an average particle size of 10 μm. 0.5 Co 0.2 Mn 0.3 O2 was used. 90 parts by mass of this positive electrode active material was mixed with 3 parts by mass of spherical carbon particles produced by pyrolysis of acetylene as a conductive assistant, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent, and the mixture was stirred for 1 hour using a stainless steel ball mill, and then coated on an aluminum current collector using a bar coater with a gap of 100 μm, dried at 80° C. in a vacuum for 12 hours or more, and then roll-pressed to form a positive electrode sheet. Furthermore, a solution prepared by dissolving 3 parts by mass of the polyether copolymer obtained in Polymerization Example 2 in 97 parts by mass of acetonitrile was applied onto the positive electrode active material layer on this sheet by knife coating, and the sheet was allowed to stand and dry at 25°C for 5 hours, and then dried in a normal pressure dryer at 60°C for 10 hours to produce a positive electrode 2 carrying 3.0 parts by mass of the polyether copolymer per 100 parts by mass of the positive electrode active material.
[0084] Using the negative electrode, separator, and non-aqueous electrolyte solution described in Example 1, the positive electrode 2 and the negative electrode were pressure-bonded via the separator to form a laminate, and the laminate was then housed in an aluminum laminate and the non-aqueous electrolyte solution was injected to produce a lithium ion secondary battery 2.
[0085] Comparative Example 1: Preparation of Lithium-ion Secondary Battery 3 <Positive electrode 3> The positive electrode active material is LiNi with an average particle size of 10 μm. 0.5 Co 0.2 Mn 0.3 O2 was used. 90 parts by mass of this positive electrode active material was mixed with 3 parts by mass of spherical carbon particles produced by pyrolysis of acetylene as a conductive assistant, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent, and the mixture was stirred for 1 hour using a stainless steel ball mill, and then coated on an aluminum current collector using a bar coater with a gap of 100 μm, dried at 80° C. in a vacuum state for 12 hours or more, and then roll-pressed to prepare a positive electrode 3.
[0086] Using the negative electrode, separator, and non-aqueous electrolyte solution described in Example 1, the positive electrode 3 and the negative electrode were pressure-bonded via the separator to form a laminate, and the laminate was then housed in an aluminum laminate and the non-aqueous electrolyte solution was injected to produce a lithium ion secondary battery 3.
[0087] Comparative Example 2: Preparation of Lithium-ion Secondary Battery 4 <Positive electrode 4> The positive electrode active material is LiNi with an average particle size of 10 μm. 0.5 Co 0.2 Mn 0.3O2 was used. 90 parts by mass of this positive electrode active material was mixed with 3 parts by mass of spherical carbon particles produced by pyrolysis of acetylene as a conductive assistant, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent, and the mixture was stirred for 1 hour using a stainless steel ball mill, and then coated on an aluminum current collector using a bar coater with a gap of 100 μm, dried at 80° C. in a vacuum for 12 hours or more, and then roll-pressed to form a positive electrode sheet. Further, on this sheet, a solution prepared by dissolving 5 parts by mass of the polyether copolymer obtained in Polymerization Example 3 in 95 parts by mass of acetonitrile was applied by knife coating onto the positive electrode active material layer, and the sheet was allowed to stand and dry at 25° C. for 5 hours, and then dried in a normal pressure dryer at 60° C. for 10 hours to produce a positive electrode 4 carrying 2.5 parts by mass of the polyether copolymer per 100 parts by mass of the positive electrode active material.
[0088] Using the negative electrode, separator, and non-aqueous electrolyte solution described in Example 1, a positive electrode 4 and a negative electrode were pressure-bonded via the separator to form a laminate, and the laminate was then housed in an aluminum laminate and the non-aqueous electrolyte solution was injected to produce a lithium ion secondary battery 4.
[0089] Comparative Example 3: Preparation of Lithium-ion Secondary Battery 5 <Positive electrode 5> The positive electrode active material is LiNi with an average particle size of 10 μm. 0.5 Co 0.2 Mn 0.3 O2 was used. 90 parts by mass of this positive electrode active material was mixed with 3 parts by mass of spherical carbon particles produced by pyrolysis of acetylene as a conductive assistant, 7 parts by mass of polyvinylidene fluoride as a binder, and 50 parts by mass of N-methyl-2-pyrrolidone as a solvent, and the mixture was stirred for 1 hour using a stainless steel ball mill, and then coated on an aluminum current collector using a bar coater with a gap of 100 μm, dried at 80° C. in a vacuum for 12 hours or more, and then roll-pressed to form a positive electrode sheet. Further, on this sheet, a solution prepared by dissolving 5 parts by mass of the polyether copolymer obtained in Polymerization Example 2 in 95 parts by mass of acetonitrile was applied by knife coating onto the positive electrode active material layer, and the sheet was allowed to stand and dry at 25°C for 5 hours, and then dried in a normal pressure dryer at 60°C for 10 hours to produce a positive electrode 5 carrying 6.2 parts by mass of the polyether copolymer per 100 parts by mass of the positive electrode active material.
[0090] Using the negative electrode, separator, and non-aqueous electrolyte solution described in Example 1, the positive electrode 5 and the negative electrode were pressure-bonded via the separator to form a laminate, and the laminate was then housed in an aluminum laminate and the non-aqueous electrolyte solution was injected to produce a lithium ion secondary battery 5.
[0091] [Evaluation of lithium-ion secondary batteries] The lithium ion secondary batteries produced in the examples and comparative examples were evaluated by the methods described below. The evaluation results are shown in Table 2. <Charge / discharge cycle test> A charge-discharge cycle test was performed 100 times at 2.5 to 4.3 V at a 2-hour discharge rate (C / 2) of the theoretical capacity using a charge-discharge evaluation device TOSCAT-3100 (Toyo Systems Co., Ltd.) to determine the discharge capacity. The larger the discharge capacity, the better the charge-discharge cycle characteristics. <Cell volume change rate> The rate of change in cell volume after the charge / discharge test was determined using the Archimedes method relative to the cell volume before the test. The smaller the rate of change in cell volume, the more gas generation is suppressed, which indicates superiority. <Rate of change in DC resistance> The initial resistance was measured by discharging at a 1 / 2 hour rate (2C) from the time the charge voltage reached 4.3V in the third charge / discharge cycle, plotting the voltage change for 10 seconds immediately after the start of discharge on the vertical axis and the discharge current value at that time on the horizontal axis, and the slope of the straight line passing through the origin was determined as the initial resistance. The rate of change in DC resistance was calculated as the ratio of the resistance after 100 cycles to the initial resistance. The smaller the rate of change in DC resistance, the more the increase in resistance value is suppressed.
[0092] [Table 2]
[0093] From Table 2, compared with Comparative Examples 1 to 3, the positive electrode defined in the present invention is superior in that gas generation and resistance value increase are suppressed because both the cell volume and the DC resistance change rate after 100 charge / discharge cycles are low. Furthermore, it is understood that the charge / discharge cycle characteristics are good because the discharge capacity is high. In addition, as shown in Comparative Example 3, although gas generation is suppressed, the initial resistance value is high, which leads to a decrease in discharge capacity, and it was also found that too much polyether copolymer support causes a decrease in performance. [Industrial Applicability]
[0094] The positive electrode of the present invention has good charge-discharge cycle characteristics, and therefore can provide an electricity storage device with excellent stability.
Claims
1. Formula (1): 【Chemistry 1】 [In the formula, R is an alkyl group having 1 to 12 carbon atoms, or -CH 2 O(CH 2 CH 2 O) 2 CH 3.] 10 to 80 mol % of a repeating unit derived from a monomer represented by the formula: Formula (2): 【Chemistry 2】 74 to 20 mol % of repeating units derived from a monomer represented by the formula: Formula (3) 【Chemistry 3】 [In the formula, R 5 is a group having an ethylenically unsaturated group. a positive electrode for an electrolyte solution electricity storage device, comprising at least a polyether copolymer having 0 to 15 mol % of a repeating unit derived from a monomer represented by the formula (I), a positive electrode current collector, a fluorine-based binder, a conductive assistant, and a positive electrode active material layer containing at least a positive electrode active material, wherein 0.01 to 5 parts by mass of the polyether copolymer is supported inside the positive electrode active material layer per 100 parts by mass of the positive electrode active material.
2. 2. The method for producing a positive electrode for an electrolyte solution storage device according to claim 1, further comprising the step of applying a polyether copolymer solution obtained by dissolving the polyether copolymer in a solvent onto a positive electrode active material layer, thereby impregnating and supporting the polyether copolymer in the positive electrode active material layer.
3. 3. The method for producing a positive electrode for an electrolyte solution storage device according to claim 2, wherein the solvent is at least one selected from the group consisting of water, alcohol, acetone, acetonitrile, methyl ethyl ketone, toluene and N-methyl-2-pyrrolidone.
4. An electricity storage device comprising the positive electrode according to claim 1.
Citation Information
Patent Citations
JP1975079025A
Injection molded bearing and its molding method
JP1987046019A
Electrode and lithium secondary battery
JP2002117860A
Nonaqueous electrolyte secondary battery
JP2012226854A
Nonaqueous electrolyte secondary battery
JP2012226937A